2015
DOI: 10.13001/1081-3810.2910
|View full text |Cite
|
Sign up to set email alerts
|

Common solutions of linear equations in a ring, with applications

Abstract: Abstract. This paper gives necessary and sufficient conditions for the existence of a common solution, and two expressions for the general common solution of the equation pair a 1 xb 1 = c1, a 2 xb 2 = c 2 , via a simpler equation p 1 xp 2 + q 1 yq 2 =c, when each element belongs to an associative ring with unit. The paper also considers the same problem in the setting of a strongly * -reducing ring. Solutions of the generalized Sylvester equation are also presented. Both the solvability conditions and the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In [4], using the generalized inverse of elements, common solutions of linear equations in a ring are discussed. Interesting research in this direction can be found in the literatures [5,16,17].…”
Section: Yue Sui Yimin Huang and Junchao Weimentioning
confidence: 99%
“…In [4], using the generalized inverse of elements, common solutions of linear equations in a ring are discussed. Interesting research in this direction can be found in the literatures [5,16,17].…”
Section: Yue Sui Yimin Huang and Junchao Weimentioning
confidence: 99%
“…Researchers have increased interest in studying matrix and operator equation and the system of it, can you see [8][9][10][11][12][13]. [28], [29] Τ𝒳 = 𝒰 and Τ 𝑖 𝒳 = 𝒰 𝑖 , 𝑖 = 1,2, 1 In [14], Zhang studied the Hermitian positive semidefinite solution of Τ𝒳𝒱 = 𝒰, 2 The Banach or Hilbert spaces was used for matrices and bounded linear operators (see, [13,[15][16][17][18][19][20][21][22]), and finding necessary conditions and sufficient conditions (N-SCs) for an existence of a combined solutions, and generalization of two equations Τ 𝑖 𝒳𝒱 𝑖 = 𝒰 𝑖 , 𝑖 = 1,2, 3 Also, the equation's solvability, as follows Τ 1 𝒳𝒱 1 + Τ 2 𝒳𝒱 2 = 𝒰, 4 Vosough and Moslehian [23] gave characterizations of the existence and representations of the solutions to the system and restricted the case of operator systems ℬ𝒳𝒜 = ℬ = 𝒜𝒳, 5…”
Section: Introductionmentioning
confidence: 99%
“…Especially, many problems in control theory can be transformed into the Sylvester matrix equations, such as singular system control [4,21], robust control [3,26], neural network [25,36]. The solvability of linear equations is a fundamental problem, and various results are developed, such as solvability conditions of linear equations for matrices over the complex field [1,2,10,11,18,22,23,[29][30][31][32][33][34]37], solvability conditions of linear equations over algebras or rings [5,6,24,27,28,35].…”
Section: Introductionmentioning
confidence: 99%